A journey to triumph: The making of THRICE project using oracle technology - Abd Ghani, Nor Farzana; Ku-Mahamud, Ku Ruhana; Mat Kasim, Maznah; Abdullah, Fader (The Clute Institute for Academic Research, 2010)
THRICE project is kicking off in February 2010, to integrate all learning systems built from the previous projects; namely. Sekolahku.net, online training solution for Malaysia's Institute for Accountancy and online training solution for Technology Park Malaysia College. All projects are owned by In-Fusion Solutions Sdn. Bhd. and are e-learning solutions, which support its core business. THRICE project will mainly leverage on the Oracle as its main technology. Integrating to new technology may not be as good as it sounds because some issues need to be considered in terms of making sure the transition process to Oracle run smoothly. Apart from that, the mobilization of staff needs to be decided in making sure THRICE project becomes a success in fulfilling the client's wish.